Particulate Matter (PM2.5) Exposure: Implications for Public Health and Respiratory Diseases in Urban and Rural Areas - Narjis Naqvi, Syeda Farwa; Mushtaq, Ali; Khan, Ehtisham; Riaz, Aqsa; Abdullah, Haris; Hameed, Rahat; Mehmood ul Hassan; Ahmed, Bilal (Indus Journal of Bioscience Research, 2025)
Fine particles smaller than 2.5 micrometers, known as particulate matter (PM2.5), are a serious threat to public health worldwide, especially when it comes to respiratory conditions. This review highlights the distinctions between urban and rural settings while synthesizing the most recent data on PM2.5 sources, exposure patterns, and health effects. PM2.5 is mostly produced by automobile emissions, industry, and construction in cities, which results in continuously high concentrations. On the other hand, transboundary pollution frequently makes PM2.5 worse in rural areas, where it is caused by burning biomass, agricultural practices, and seasonal dust. Through processes like oxidative stress, inflammation, and epigenetic modifications, PM2.5 exposure causes both acute respiratory problems like bronchitis and asthma flare-ups as well as chronic illnesses like lung cancer and chronic obstructive pulmonary disease (COPD). While rural communities experience seasonal spikes and substantial indoor pollution from biomass combustion, urban populations are exposed on a chronic basis. Children, the elderly, and low-income groups are among the vulnerable groups that suffer disproportionately. Important discoveries highlight the pressing need for improved air quality monitoring, more stringent laws, and customized interventions to lessen the negative health effects of PM2.5. To improve our understanding of toxicity mechanisms and guide policy, future research should focus on long-term exposure studies, the impact of climate change on PM2.5 dynamics, and integrative techniques like multi-omics. In order to address urban-rural disparities and lessen the effects on global health, sustainable, context-specific solutions are essential.